Formulation of Cushion Preparations from Duck Egg Shells and SPF Value Testing Using the UV-Vis Spectrophotometry Method - Fitriyana, Rahma; Fauzi, Muhammad; Ramadhani, Juwita (Jurnal FARMASIMED (JFM), 2024)
The effectiveness of a sunscreen can be indicated by the value of Sun Protection Factor (SPF), which is defined as the amount of UV energy needed. Cream is a semi-solid dosage from containing one or more medicinal ingredients dissolved or dispersed in a suitable base material. One of the compounds contained in eggshells is CaCO3. Calcium carbonate is necessary for cell regeneration and as a barrier to ultaviolet (UV) rays. This study aims to determine the potential SPF in duck eggshell, the SPF value contained in the cushion and the physical properties of the cushion preparation. Here, three variations of duck egg shell flour concentrations (4%, 8% and 16%) were made, tested in vitro using UV-Vis spectrophotometry from a wavelength of 290-320 nm every 5 nm and the absorbance was measured and the properties were tested. and physical stability (organoleptic, pH, spreadability, stickiness, viscosity, centrifugation, and Freeze-Thaw Cycling for 6 days (3 cycles) at temperatures of 40°C and 4°C). Our research results show that the duck egg shell formulation cannot be used as an SPF product. Formula 1 has an SPF value of 2.6, formula 2 has an SPF value of 3.3 and formula 3 has an SPF value of 3. The test results for the properties and stability of formula 2 with a concentration of 8% duck egg shell flour show the most stable results compared to the other 2 formulas